(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
The present research is concerned with the investigations of the paleoenvironment of the benthic foraminifera and their diversity in St. Martin’s Island, Bangladesh. About 300 specimens of foraminifera were collected from three sampling sites of the island. Among them 44 species, 39 genera and 25 families were identified which were mostly benthic in origin. Astrorhiza, Elphidium, Cyclammina, Cibicides, and Eponoide were the most abundant genera all over the island based on their relative abundance and frequency of occurrence. Among the three sections, Uttar Para can be designated as Astrorhiza- Elphidium assemblage zone, Maddhya Para as Astrorhiza- Elphidium assemblage zone and Dakkhin para as Astrorhiza-Cibicides assemblage zone. The relative abundance chart of foraminifera and its correlation with the Saraswati and Srinivasan (2016) model diagram indicates that the paleoenvironment signature of the island belongs to the inner shelf to the middle shelf region. The plot of shell-type ratios on Murray’s ternary diagram also suggests the same paleoenvironment. Gibson’s index of oceanity was 2% which indicates a shelf environment where the diversity of benthic foraminifera is high. Murray’s index of diversity for all three sections was above the range V, which indicates the normal salinity of the ocean. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(1), 2020, P 25-30